Short term living conditions and long term prospects of immigrant children in Germany - Joachim R. Frick; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
In Germany the foreign born population is made up of foreigners and so called "ethnic Germans" who migrated from eastern European countries to Germany. While the first group is confronted with problems arising from the typical German concept of ethnicity and citizenship, the latter are entitled to a German passport immediately after crossing the border. About one half of the immigrants who entered Germany since 1984 are ethnic Germans. Thus, any analysis of the living conditions of immigrant children in comparison to native born German children must take into account the heterogeneity of immigrants in Germany as well as the respective institutional settings. Throughout the last decade the financial situation of children in Germany has been marked by increasing problems: in 1997 the population share of children living in households receiving welfare payments was about twice as high as the respective share for the entire population. Poverty head count rates (based on a poverty threshold of 50 percent of median equivalent income) clearly increased over this period from about 10 percent to more than 15 percent in 1996. The central aim of this paper is to analyze differences between native and foreign children within this process. Our comparative analyses are based on the different sub-samples of the German Socio-Economic Panel Study (GSOEP). With respect to non-monetary as well as monetary indicators there are - although the German transfer system is strong - remarkable differences in living conditions between native born German children and those born to immigrants and foreigners. On average we find that children in Germany to have lost out in terms of their relative income position over the period 1985/86 to 1995/96, thus pushing the need for targeted social policy. This should cover targeted financial transfers as well as an improvement of day care for children. Although there are some signs of improvement concerning the integration process of foreigners? children over this period, the majority of this group still lives in rather poor conditions. There is no formal "discrimination" of immigrant children by the German school system. But due to the strong intergenerational correlation of educational attainment it is a problem that the educational level of immigrant parents as well as of foreign parents living in Germany is still clearly below the population average, although there are some signs of improvement. As a result of the low educational level of their parents we find children born to immigrants and foreigners in Germany to be on less favorable educational tracks more often than native born German children. The long-term problem arising from this will be a persistently high share of rather poorly qualified persons in the future work force, who will face severe labor market problems and as such will be a problem for the German economy as a whole. In other words: the German educational system – including pre-school, school and vocational training – needs to provide equal opportunities to all children regardless of their social background. If necessary, there should be additional incentives for children born to immigrants and foreigners to overcome language disadvantages. – – Der im Ausland geborene Teil der in Deutschland lebenden Bevölkerung besteht aus Ausländern und Aussiedlern, die aus osteuropäischen Ländern nach Deutschland emigriert sind. Während die erste Gruppe mit Problemen konfrontiert ist, die aus dem typisch deutschen Konzept von Ethnizität und Staatsangehörigkeit resultieren, erhält die zweite Gruppe quasi beim Grenzübertritt einen deutschen Pass. Etwa die Hälfte der Immigranten, die seit 1984 nach Deutschland kamen, sind der Gruppe der Aussiedler zuzurechnen. Daher muss jede Analyse der Lebensbedingungen von Immigranten-Kindern im Vergleich zu in Deutschland geborenen Kindern deutscher Eltern sowohl die Heterogenität der Immigranten als auch institutionelle Rahmenbedingungen beachten. Während der letzten zehn bis fünfzehn Jahre ist die finanzielle Situation aller in Deutschland lebenden Kinder von immer größer werdenden Problemen gekennzeichnet: Als Resultat ist im Jahre 1997 der Anteil von Kindern in Haushalten, die Sozialhilfe erhalten ca. zweimal so hoch wie der entsprechende Anteil in der gesamten Bevölkerung. Die Armutsraten (basierend auf einer Armuts-Grenze von 50% des mittleren Äquivalenzeinkommens) sind innerhalb einer Dekade von 10% auf mehr als 15% deutlich angestiegen. Unsere empirische Analyse basiert auf verschiedenen Teilstichproben des Sozio-oekonomischen Panels (GSOEP). Nicht-monetäre und monetäre Indikatoren belegen ? trotz der Stärken des deutschen Transfer-Systems ? beachtliche Differenzen zwischen den Lebensbedingungen der Kindern von Immigranten und Ausländern im Vergleich zu Kindern authochthoner Eltern. Im Durchschnitt hat sich relative Einkommensposition der Kinder in Deutschland über den Zeitraum von 1985/86 bis 1995/96 verschlechtert, was eine Notwendigkeit einer gezielten Sozialpolitik unterstreicht. Diese sollte sowohl finanzielle Transfers als auch eine Verbesserung einer außerhäusigen Kinderbetreuung beinhalten. Obwohl es Zeichen einer Verbesserung hinsichtlich des Integrationsprozesses von ausländischen Kindern über diesen Zeitraum gibt, lebt die Mehrheit dieser Gruppe nach wie vor in deutlich unterdurchschnittlichen Bedingungen. Innerhalb des deutschen Schulsystems gibt es keine formale "Diskriminierung" von Immigranten-Kindern. Angesichts der starken intergenerationalen Bildungskorrelation birgt das unterdurchschnittliche Bildungsniveau der in Deutschland lebenden erwachsenen Immigranten und Ausländer - trotz leichter Verbesserungen im langjährigen Vergleich ? jedoch große Probleme für deren Kinder. Als Ergebnis des geringen Bildungsniveaus ihrer Eltern sind Kinder von Immigranten und Ausländern deutlich häufiger auf ungünstigeren Bildungswegen zu finden, mit entsprechenden Problemen bei der Integration in den deutschen Arbeitsmarkt und die Gesellschaft insgesamt. Daher muss das deutsche Bildungssystem (einschließlich Kindergarten, Vorschule, Schule und Berufsausbildung) allen Kindern effektiv gleiche Startchancen geben ohne Ansehen des sozialen Hintergrundes. Neben Verbesserungen im Zugang zu Ausbildungsförderung (z.B. BAFöG) erscheinen dabei auch zusätzliche Anreize für Immigranten- und Ausländer-Kinder zur Verbesserung ihrer deutschen Sprachkenntnisse von großer Bedeutung.
Keywords: I3; I2; J1; 330; Children; Immigration; Living Conditions; Income Position; Poverty; Migranten; Kinder; Ausländer; Einkommensverteilung; Lebensstandard; Armut; Schätzung; Deutschland